ISLAM GAYO: STUDI TENTANG AKULTURASI ISLAM DENGAN BUDAYA LOKAL DI KABUPATEN ACEH TENGAH - Ali Mustafa; Rahmat Hidayat (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
This paper explores the acculturation of Islam with local culture in the Gayo highlands, district of Central Aceh. The study focused on both the process of acculturation of Islam and local culture in the ceremonies of birth, marriage and death. In this process, Gayonization of Islam is dominant in comparison to Islamization of Gayo’s culture. In Gayonization of Islam, the terms, actions, and equipments used in the ritual is a purely Gayo’s culture, but Islamic values and teachings are inserted in it. The acculturation process occurred in four stages such as accomodating islamic preaching, identification, Gayonization, and implementation. Furthermore, the acculturation of Islam with Gayo’s culture in and the ceremonies of birth, marriage, and death, can be grouped in three forms: 1) the acculturation of Islamic values with customary objects, in which the objects are ascribed as symbols of Islamic values; 2) the acculturation of Islamic values with the traditions, in which customary practice are attributed as a symbol of Islamic values; and 3) the acculturation of Islam with customary practice, in which customary practice is based on Islamic teachings. At the first and second forms, it can be said that there is a shift from a custom-based meaning to Islam-based meaning (substitution of meaning). While at the third form, occurred the infusion of Islamic values to traditional ritual (addition to the rites).